Grain corrosion method for nickel-silicon alloy target blank

Through the combination of mechanical polishing, electrolytic polishing and corrosion treatment, the nickel-silicon alloy material is processed, which solves the problem of difficult to clearly display the metallographic structure of nickel-silicon alloy in the prior art, and achieves the clear manifestation of metallographic structure and the stability and controllability of the process.

CN119845688APending Publication Date: 2025-04-18KONFOONG MATERIALS INTERNATIONAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510036766.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

There is a lack of effective grain corrosion methods suitable for nickel-silicon alloy materials in the prior art, and it is difficult to clearly display its metallographic structure.

Method used

The nickel-silicon alloy target blank is treated by a combination of mechanical polishing treatment, electrolytic polishing treatment and corrosion treatment. The specific steps include electrolytic polishing treatment using a polishing liquid of a specific ratio and corrosion treatment through a corrosion liquid of a specific ratio to reveal the grain boundaries of the metal phase structure.

Benefits of technology

This method can significantly improve the metallographic structure display effect of nickel-silicon alloy, with simple operation, stable process, strong controllability, and is suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845688A_ABST
    Figure CN119845688A_ABST
Patent Text Reader

Abstract

The invention provides a grain corrosion method for a nickel-silicon alloy target blank, which comprises the following steps: sequentially carrying out mechanical polishing treatment, electrolytic polishing treatment and corrosion treatment on the nickel-silicon alloy target blank to obtain a treated nickel-silicon alloy; a polishing solution used in the electrolytic polishing treatment comprises ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8): (0.5-1.5): (1-3). The grain corrosion method is easy to operate, the used polishing solution and corrosion solution are simple in formula and good in corrosion effect, and the metallographic structure display problem of the nickel-silicon alloy is well solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal grain detection, and in particular to a grain corrosion method for a nickel-silicon alloy target material blank. Background Art

[0002] Metallography refers to the chemical composition of a metal or alloy and the physical and chemical states of various components within the alloy. Grain boundaries refer to the interface between crystals with the same structure but different orientations. On the crystal interface, the atomic arrangement transitions from one orientation to another, so the atomic arrangement at the grain boundary is in a transitional state. The contact surface between grains is called a grain boundary. The internal structure of metal materials is directly and closely related to material properties such as hardness, strength, and ductility, and metallographic observation is the most direct and effective method to study the internal structure of metal materials.

[0003] CN112981406A discloses a surface grain corrosion method for an IN718C nickel-based high-temperature alloy aviation bearing seat, comprising the following steps: grinding the surface of the casting to remove the corrosion layer; sandblasting to remove pollutants on the surface of the casting so that the surface of the casting is in an activated state; chemically etching the casting after being soaked in hot water in a corrosion solution prepared by copper sulfate pentahydrate, hydrochloric acid solution and water; swing cleaning with cold water until no corrosion solution remains on the surface; rinsing with a high-pressure water gun after neutralizing the casting; and surface inspection after hot water soaking and drying. Compared with the existing corrosion method using a ratio of copper sulfate, hydrochloric acid and water, and a bleaching method using hydrofluoric acid and nitric acid, the operation steps are simplified and safe, the corrosion process parameters are more controllable, the process is stable, the surface grains are clearly and evenly displayed, the production repeatability is good and the cost is low, and the qualified rate of corrosion production is improved.

[0004] CN112525903A discloses a method for corrosion visualization of high-strength austenite grain size. After the sample is heated at a constant temperature of 890±10℃ for at least 1h, it is taken out and quickly quenched in water; the quenched sample is ground and polished in turn; the polished sample is placed in an etchant at 85℃ for 9min, and during the entire corrosion process, the sample surface is continuously wiped with a non-woven fabric; the sample is taken out, rinsed with anhydrous ethanol, and then blown dry. The metallographic photograph of the sample after the pretreatment step shows clear grain boundaries and no martensite phase, and the operation is simple.

[0005] CN105018933A discloses a method for macro grain corrosion of single crystal high temperature alloy castings containing Re and / or Ru, which belongs to the field of quality inspection technology of core hot end components of aviation, aerospace engines and civil gas engines - turbine blades. The corrosive liquid used in the method includes hydrochloric acid, nitric acid, sulfuric acid, water, copper sulfate and ferric chloride; first, the casting is placed in a corrosion tank, the corrosive liquid is poured into the corrosion tank, and the corrosion reaction is 20-30 minutes; after the corrosion reaction is completed, the casting is taken out, and the black product remaining on the surface of the casting after the reaction is brushed off with a brush, and then rinsed with clean water to obtain a bright surface macroscopic structure, and the macroscopic structure can be observed. The method uses different corrosive media in the corrosive agent to corrode the grain boundary and the matrix or strengthening phase at different speeds at the same time, and the grains with different orientations show obvious symmetry differences, ensuring the good appearance of various surface defects in the single crystal blade.

[0006] However, the above-mentioned grain corrosion method is not applicable to nickel-silicon alloy materials.

[0007] Therefore, developing a grain corrosion method for nickel-silicon alloy target blanks is of great significance for studying the internal structure of nickel-silicon alloy materials. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a method for grain corrosion of a nickel-silicon alloy target material blank. By sequentially performing mechanical polishing treatment, electrolytic polishing treatment and corrosion treatment on the nickel-silicon alloy target material blank, the display of the grains in the alloy target material blank is made clearer; and the polishing liquid and the etching liquid used have simple formulas, and the corrosion detection time is short, which well solves the problem of metallographic structure display of nickel-silicon alloy.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] The present invention provides a method for grain corrosion of a nickel-silicon alloy target material blank, the method comprising:

[0011] The nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, electrolytic polishing treatment and corrosion treatment in sequence to obtain a treated nickel-silicon alloy;

[0012] The polishing liquid used in the electrolytic polishing process includes ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8):(0.5-1.5):(1-3).

[0013] The grain corrosion method of the nickel-silicon alloy target material blank of the present invention first performs mechanical polishing on the nickel-silicon alloy target material blank, then performs electrolytic polishing with a specific polishing liquid, and finally performs corrosion treatment, which well solves the problem of metallographic structure display of the nickel-silicon alloy. Under a metallographic microscope, it can be observed that the metallographic structure grain boundary display effect of the nickel-silicon alloy is good.

[0014] The polishing liquid used in the electrolytic polishing treatment of the present invention includes ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8):(0.5-1.5):(1-3), for example, it can be 6:0.5:1, 6.5:0.7:1.5, 6.8:1:2, 7:1.1:2.5, 7.5:1.3:2.7 or 8:1.5:3, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] The polishing liquid used in the electrolytic polishing treatment of the present invention includes ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8):(0.5-1.5):(1-3), wherein ethylene glycol monobutyl ether is an excellent surfactant and can remove impurities such as oil stains on the surface of the nickel-silicon alloy target material blank; if the polishing liquid does not contain perchloric acid, the electrolyte cannot be polished, and the metallographic structure cannot be observed under a metallographic microscope.

[0016] Preferably, the mechanical polishing process comprises polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence.

[0017] Preferably, water is used as a wetting agent during the mechanical polishing process.

[0018] Preferably, the total time of the mechanical polishing treatment is 5 to 10 minutes, for example, it can be 5 minutes, 5.5 minutes, 6 minutes, 7 minutes, 8 minutes or 10 minutes, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, after the mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried.

[0020] Preferably, the cleaning liquid used in the first cleaning comprises water.

[0021] Preferably, the voltage of the electrolytic polishing treatment is 30-36V, for example, 30V, 31V, 32V, 34V, 35V or 36V, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the electrolytic polishing treatment time is 30 to 40 seconds, for example, it can be 30 seconds, 32 seconds, 34 seconds, 36 seconds, 38 seconds or 40 seconds, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] The present invention preferably adopts a voltage of 30 to 36 V and a time of 30 to 40 s for the electrolytic polishing treatment. The voltage and time cooperate with each other to achieve good polishing of the nickel-silicon alloy target blank, and the metallographic structure revealed by corrosion is clear and easy to observe.

[0024] Preferably, the concentration of ethanol is 95% to 99%, for example, 95%, 95.5%, 96%, 97%, 98% or 99%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the concentration of ethylene glycol monobutyl ether is 95% to 99%, for example, 95%, 95.5%, 96%, 97%, 98% or 99%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the concentration of perchloric acid is 70% to 72%, for example, 70%, 70.5%, 70.8%, 71%, 71.5% or 72%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the etching solution used in the etching treatment includes nitric acid and hydrofluoric acid in a volume ratio of (1-3):(0.5-1.5), for example, it can be 1:0.5, 1.5:0.7, 2:0.9, 2.5:1, 2.8:1.3 or 3:1.5, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] The present invention preferably uses a corrosion solution comprising nitric acid and hydrofluoric acid in a volume ratio of (1-3): (0.5-1.5). The role of nitric acid is to dissolve the atoms of the surface layer into the etchant, and then chemically dissolve the grain boundary to form a groove-shaped grain boundary. The role of hydrofluoric acid is to remove the oxide on the metal surface to make the metal surface smoother. The combination of the two can well show the grain boundary. When there is less nitric acid in the corrosion solution, the grain boundary will not be obvious; when there is more nitric acid in the corrosion solution, it will cause over-corrosion.

[0029] Preferably, the corrosion treatment time is 25 to 35 seconds, for example, 25 seconds, 28 seconds, 30 seconds, 32 seconds, or 35 seconds, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the concentration of nitric acid is 65% to 68%, for example, 65%, 65.5%, 66%, 66.5%, 67% or 68%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the concentration of the hydrofluoric acid is 40% to 45%, for example, 40%, 41%, 42%, 43%, 44% or 45%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] The concentrations of various solutions involved in the present invention are all mass concentrations.

[0033] Preferably, the treated nickel-silicon alloy is subjected to a second cleaning and its microstructure is observed under a metallographic microscope;

[0034] Preferably, the cleaning liquid used in the second cleaning comprises water.

[0035] As a preferred technical solution of the present invention, the grain corrosion method comprises:

[0036] After the nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried; then, an electrolytic polishing treatment is performed at a voltage of 30 to 36 V for 30 to 40 seconds and an etching treatment is performed for 25 to 35 seconds to obtain a treated nickel-silicon alloy; after the treated nickel-silicon alloy is subjected to a second cleaning, the microstructure is observed under a metallographic microscope;

[0037] The mechanical polishing process includes polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence; water is used as a wetting agent during the mechanical polishing process; and the total time of the mechanical polishing process is 5 to 10 minutes;

[0038] The cleaning liquid used in the first cleaning includes water;

[0039] The polishing liquid used in the electrolytic polishing treatment includes ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8):(0.5-1.5):(1-3); the concentration of the ethanol is 95%-99%; the concentration of the ethylene glycol monobutyl ether is 95%-99%; the concentration of the perchloric acid is 70%-72%;

[0040] The etching solution used in the etching treatment includes nitric acid and hydrofluoric acid in a volume ratio of (1-3):(0.5-1.5); the concentration of the nitric acid is 65%-68%; the concentration of the hydrofluoric acid is 40%-45%;

[0041] The cleaning liquid used in the second cleaning includes water.

[0042] Compared with the prior art, the present invention has at least the following beneficial effects:

[0043] The grain corrosion method of the nickel-silicon alloy target material blank provided by the present invention is simple to operate, has simple formulas of the polishing liquid and the corrosion liquid used, has good corrosion effect, has good metallographic structure grain boundary display effect, has stable process, has strong controllability, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 1 of the present invention.

[0045] Figure 2 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 2 of the present invention.

[0046] Figure 3 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 3 of the present invention.

[0047] Figure 4 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 4 of the present invention.

[0048] Figure 5 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 5 of the present invention.

[0049] Figure 6 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 6 of the present invention.

[0050] Figure 7 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 7 of the present invention.

[0051] Figure 8 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 8 of the present invention.

[0052] Fig. 9 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Example 9 of the present invention.

[0053] Fig.10 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Comparative Example 2 of the present invention.

[0054] Fig.11 This is a metallographic structure picture of the nickel-silicon alloy target material blank in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0056] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0057] Example 1

[0058] This embodiment provides a method for grain corrosion of a nickel-silicon alloy target material blank, the method comprising:

[0059] After the nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried; then, an electrolytic polishing treatment at a voltage of 33V is performed for 30 seconds and an etching treatment is performed for 30 seconds to obtain a treated nickel-silicon alloy; after the treated nickel-silicon alloy is subjected to a second cleaning, the microstructure is observed under a metallographic microscope;

[0060] The mechanical polishing process includes polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence; water is used as a wetting agent during the mechanical polishing process; and the total time of the mechanical polishing process is 8 minutes;

[0061] The cleaning liquid used in the first cleaning is water;

[0062] The polishing liquid used in the electrolytic polishing treatment is ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of 7:1:2; the concentration of the ethanol is 96%; the concentration of the ethylene glycol monobutyl ether is 97%; the concentration of the perchloric acid is 71%;

[0063] The etching solution used in the etching treatment is nitric acid and hydrofluoric acid in a volume ratio of 2:1; the concentration of the nitric acid is 67%; the concentration of the hydrofluoric acid is 43%;

[0064] The cleaning liquid used in the second cleaning is water.

[0065] Example 2

[0066] This embodiment provides a method for grain corrosion of a nickel-silicon alloy target material blank, the method comprising:

[0067] After the nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried; then, an electrolytic polishing treatment at a voltage of 30V is performed for 40s and an etching treatment is performed for 35s to obtain a treated nickel-silicon alloy; after the treated nickel-silicon alloy is subjected to a second cleaning, the microstructure is observed under a metallographic microscope;

[0068] The mechanical polishing process includes polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence; water is used as a wetting agent during the mechanical polishing process; and the total time of the mechanical polishing process is 5 minutes;

[0069] The cleaning liquid used in the first cleaning is water;

[0070] The polishing liquid used in the electrolytic polishing treatment is ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of 6:1.5:1; the concentration of the ethanol is 99%; the concentration of the ethylene glycol monobutyl ether is 95%; the concentration of the perchloric acid is 72%;

[0071] The etching solution used in the etching treatment is nitric acid and hydrofluoric acid in a volume ratio of 3:0.5; the concentration of the nitric acid is 65%; the concentration of the hydrofluoric acid is 40%;

[0072] The cleaning liquid used in the second cleaning is water.

[0073] Example 3

[0074] This embodiment provides a method for grain corrosion of a nickel-silicon alloy target material blank, the method comprising:

[0075] After the nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried; then, an electrolytic polishing treatment at a voltage of 36V is performed for 30s and an etching treatment is performed for 25s to obtain a treated nickel-silicon alloy; after the treated nickel-silicon alloy is subjected to a second cleaning, the microstructure is observed under a metallographic microscope;

[0076] The mechanical polishing process includes polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence; water is used as a wetting agent during the mechanical polishing process; and the total time of the mechanical polishing process is 5 minutes;

[0077] The cleaning liquid used in the first cleaning is water;

[0078] The polishing liquid used in the electrolytic polishing treatment is ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of 8:0.5:3; the concentration of the ethanol is 95%; the concentration of the ethylene glycol monobutyl ether is 99%; the concentration of the perchloric acid is 70%;

[0079] The etching solution used in the etching treatment is nitric acid and hydrofluoric acid in a volume ratio of 1:0.5; the concentration of the nitric acid is 65%; the concentration of the hydrofluoric acid is 45%;

[0080] The cleaning liquid used in the second cleaning is water.

[0081] Example 4

[0082] This embodiment provides a method for grain corrosion of a nickel-silicon alloy target material blank. The grain corrosion method is the same as that of Embodiment 1 except that the voltage of the electrolytic polishing treatment is 20 V and the time is 50 s.

[0083] Example 5

[0084] This embodiment provides a method for grain corrosion of a nickel-silicon alloy target material blank. The grain corrosion method is the same as that of Embodiment 1 except that the voltage of the electrolytic polishing treatment is 40 V and the time is 20 s.

[0085] Example 6

[0086] This embodiment provides a method for grain etching of a nickel-silicon alloy target material blank. The grain etching method is the same as that of Embodiment 1 except that the concentration of perchloric acid in the polishing liquid used in the electrolytic polishing process is 60%.

[0087] Example 7

[0088] This embodiment provides a method for grain etching of a nickel-silicon alloy target material blank. The grain etching method is the same as that of Embodiment 1 except that the concentration of perchloric acid in the polishing liquid used in the electrolytic polishing process is 80%.

[0089] Example 8

[0090] This embodiment provides a method for grain etching of a nickel-silicon alloy target material blank. The grain etching method is the same as that of Embodiment 1 except that the etching solution used in the etching treatment is nitric acid and hydrofluoric acid in a volume ratio of 0.5:1.

[0091] Example 9

[0092] This embodiment provides a method for grain etching of a nickel-silicon alloy target material blank. The grain etching method is the same as that of Embodiment 1 except that the etching solution used in the etching treatment is nitric acid and hydrofluoric acid in a volume ratio of 5:1.

[0093] Comparative Example 1

[0094] This comparative example provides a method for grain etching of a nickel-silicon alloy target material blank. The grain etching method is the same as Example 1 except that the polishing liquid used in the electrolytic polishing process does not include perchloric acid.

[0095] Comparative Example 2

[0096] This comparative example provides a method for grain etching of a nickel-silicon alloy target material blank, which is the same as Example 1 except that the polishing liquid used in the electrolytic polishing process is ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of 7:0.1:2.

[0097] Comparative Example 3

[0098] This comparative example provides a method for grain etching of a nickel-silicon alloy target material blank. The grain etching method is the same as Example 1 except that the polishing liquid used in the electrolytic polishing process is ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of 7:3:2.

[0099] The microstructure of the nickel-silicon alloy after treatment in the above embodiments and comparative examples was observed under a metallographic microscope, and the observation results are shown in Table 1.

[0100] Table 1

[0101] Observations Example 1 Clear grains, complete images, no defects Example 2 Clear grains, complete images, no defects Example 3 Clear grains, complete images, no defects Example 4 Grain boundary over-corrosion, image has scratches Example 5 The grain boundary is not clear and the image is dark Example 6 The grain boundary is not obvious and the image is dark Example 7 Grain boundary corrosion Example 8 Grain boundaries are not obvious Example 9 Grain boundary corrosion Comparative Example 1 Unable to display grain status Comparative Example 2 Unable to display grain status Comparative Example 3 Unclear grain boundaries

[0102] From Table 1 we can see that:

[0103] (1) The nickel-silicon alloys treated in Examples 1 to 3 were observed under a metallographic microscope. The metallographic structure pictures are as follows: Figures 1 to 3 As shown, the grains are clear, the image is complete, and there is no defect, which indicates that the grain corrosion method of the nickel-silicon alloy target material blank provided by the present invention has a good corrosion effect and a good metallographic structure grain boundary display effect;

[0104] (2) The metallographic structure picture of Example 4 is as follows Figure 4 As shown, since the voltage of the electrolytic polishing treatment is relatively low at 20V, scratches will be caused on the image, and the time is relatively long at 50s, which will cause excessive corrosion of the grain boundaries; the metallographic structure picture of Example 5 is shown in Figure 5 As shown, due to the high voltage of electrolytic polishing, which is 40V, the grain boundary image will be dark, and the short time, which is 20s, will cause the grain boundary to be unclear;

[0105] (3) The concentration of perchloric acid in the polishing liquid used in the electrolytic polishing process in Example 6 is 60%. The metallographic structure picture is as follows: Figure 6 As shown, it can be seen that the grain boundary is not obvious and the image is dark; the concentration of perchloric acid in the polishing liquid used in the electrolytic polishing process in Example 7 is 80%, and the metallographic structure picture is as shown Figure 7 As shown, it can be seen that the grain boundary is over-corroded;

[0106] (4) The etching solution used in the etching treatment in Example 8 is nitric acid and hydrofluoric acid in a volume ratio of 0.5:1. The metallographic structure picture is as follows Figure 8 As shown, it can be seen that the grain boundary is not obvious; the etching solution used in the etching treatment in Example 9 is nitric acid and hydrofluoric acid with a volume ratio of 5:1, and the metallographic structure picture is as follows Fig. 9 As shown, it can be seen that the grain boundary is over-corroded;

[0107] (5) In Comparative Example 1, the polishing liquid used in the electrolytic polishing process does not include perchloric acid, which will result in the electrolyte being unable to perform polishing, and thus the metallographic structure cannot be observed under a metallographic microscope;

[0108] (6) The polishing liquid used in the electrolytic polishing treatment of Comparative Example 2 is ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of 7:0.1:2. The content of ethylene glycol monobutyl ether is relatively small, and impurities such as oil stains on the surface of the nickel-silicon alloy target material cannot be removed well, which leads to the inability to display the grain situation. The metallographic structure picture is as follows: Fig.10As shown; Comparative Example 3 electrolytic polishing treatment using a polishing liquid volume ratio of 7:3:2 ethanol, ethylene glycol monobutyl ether and perchloric acid, wherein the content of ethylene glycol monobutyl ether is relatively high, the metallographic structure picture as shown Fig.11 As shown, the grain boundaries are not clear, which is not conducive to subsequent observation and analysis.

[0109] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for grain corrosion of a nickel-silicon alloy target blank, characterized in that: The grain corrosion method comprises: The nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, electrolytic polishing treatment and corrosion treatment in sequence to obtain a treated nickel-silicon alloy; The polishing liquid used in the electrolytic polishing process includes ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8):(0.5-1.5):(1-3).

2. The grain etching method according to claim 1, characterized in that: The mechanical polishing process includes polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence.

3. The grain etching method according to claim 1 or 2, characterized in that: Water is used as a wetting agent during the mechanical polishing process.

4. The grain etching method according to any one of claims 1 to 3, characterized in that: The total time of the mechanical polishing process is 5 to 10 minutes; Preferably, after the mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried; Preferably, the cleaning liquid used in the first cleaning comprises water.

5. The grain etching method according to any one of claims 1 to 4, characterized in that: The voltage of the electrolytic polishing treatment is 30 to 36 V; Preferably, the electrolytic polishing treatment time is 30 to 40 seconds.

6. The grain etching method according to any one of claims 1 to 5, characterized in that: The concentration of the ethanol is 95% to 99%; Preferably, the concentration of ethylene glycol monobutyl ether is 95% to 99%; Preferably, the concentration of the perchloric acid is 70% to 72%.

7. The grain etching method according to any one of claims 1 to 6, characterized in that: The etching solution used in the etching treatment includes nitric acid and hydrofluoric acid in a volume ratio of (1-3):(0.5-1.5); Preferably, the corrosion treatment time is 25 to 35 seconds.

8. The grain etching method according to any one of claims 1 to 7, characterized in that: The concentration of the nitric acid is 65% to 68%; Preferably, the concentration of the hydrofluoric acid is 40% to 45%.

9. The grain etching method according to any one of claims 1 to 8, characterized in that: After the treated nickel-silicon alloy is cleaned for the second time, the microstructure is observed under a metallographic microscope; Preferably, the cleaning liquid used in the second cleaning comprises water.

10. The grain etching method according to any one of claims 1 to 9, characterized in that: The grain corrosion method comprises: After the nickel-silicon alloy target material blank is subjected to mechanical polishing treatment, the nickel-silicon alloy target material blank is first cleaned and dried; then, an electrolytic polishing treatment is performed at a voltage of 30 to 36 V for 30 to 40 seconds and an etching treatment is performed for 25 to 35 seconds to obtain a treated nickel-silicon alloy; after the treated nickel-silicon alloy is subjected to a second cleaning, the microstructure is observed under a metallographic microscope; The mechanical polishing process includes polishing the nickel-silicon alloy target material blank using 240#, 1000# and 2000# water sandpaper in sequence; water is used as a wetting agent during the mechanical polishing process; and the total time of the mechanical polishing process is 5 to 10 minutes; The cleaning liquid used in the first cleaning includes water; The polishing liquid used in the electrolytic polishing treatment includes ethanol, ethylene glycol monobutyl ether and perchloric acid in a volume ratio of (6-8):(0.5-1.5):(1-3); the concentration of the ethanol is 95%-99%; the concentration of the ethylene glycol monobutyl ether is 95%-99%; the concentration of the perchloric acid is 70%-72%; The etching solution used in the etching treatment includes nitric acid and hydrofluoric acid in a volume ratio of (1-3):(0.5-1.5); the concentration of the nitric acid is 65%-68%; the concentration of the hydrofluoric acid is 40%-45%; The cleaning liquid used in the second cleaning includes water.

Citation Information

Patent Citations

  • Macrograin corrosion method for monocrystal high-temperature alloy casting containing Re and / or Ru

    CN105018933A

  • Corrosion display method for austenite grain size of high-strength steel

    CN112525903A

  • Surface grain corrosion method for IN718C nickel-based superalloy aviation bearing seat

    CN112981406A